Deciphering the Regulatory Network between the SREBP Pathway and Protein Secretion in Neurospora crassa - Lina Qin (American Society for Microbiology, 2017)
ABSTRACT Sterol regulatory element binding proteins (SREBPs) are conserved from yeast to mammalian cells and function in the regulation of sterol homeostasis. In fungi, the SREBP pathway has been implicated in the adaptation to hypoxia and in virulence. In Neurospora crassa and Trichoderma reesei, the SREBP pathway also negatively regulates protein secretion under lignocellulolytic conditions. Here we utilized global transcriptional profiling combined with genetic and physiological analyses to address the regulatory link between the SREBP pathway and protein secretion in N. crassa. Our results demonstrated that the function of the SREBP pathway in ergosterol biosynthesis and adaptation to hypoxia was conserved in N. crassa. Under lignocellulolytic conditions, the SREBP pathway was highly activated, resulting in the reduced expression of lytic polysaccharide monooxygenases, which require molecular oxygen for catalytic activity. Additionally, activation of the SREBP pathway under lignocellulolytic conditions repressed a set of genes predicted to be involved in the endoplasmic reticulum stress response. Here we show that the inability of a hac-1 mutant, which bears a deletion of the major regulator of the unfolded protein response (UPR), to efficiently produce cellulases and utilize cellulose was suppressed by mutations in the SREBP pathway. The analyses presented here demonstrated new SREBP pathway functions, including linkages to the UPR, and provide new clues for genetic engineering of filamentous fungi to improve their production of extracellular proteins. IMPORTANCE The role of SREBP transcription factors in the regulation of sterol biosynthesis is conserved from humans to yeast. In filamentous fungi, this pathway regulates the secretion of lignocellulolytic enzymes during plant biomass deconstruction. Here we show that the SREBP pathway in Neurospora crassa regulates the production of specific cellulases, lytic polysaccharide monooxygenases that utilize molecular oxygen. Via global transcriptional profile and genetic analyses, a relationship between the SREBP pathway and the unfolded protein response (UPR) pathway was revealed, suggesting a regulatory interplay of these two pathways in the trafficking of plant biomass-degrading enzymes. These findings have implications for our understanding of the cross talk of the SREBP and UPR pathways in other organisms and will guide the rational engineering of fungal strains to improve cellulolytic enzyme production.